Clinically oriented anatomy - Moore, Keith L; Agur, Anne M. R; Dalley, Arthur F; Moore, Marianne (Lippincott, Williams & Wilkins, 2006)
A university textbook that focuses on human clinical anatomy.
Keywords: Anatomy; anatomie